God in the Narrative of the Zindiq’s Literature - Ahmad Kholil (Arabic Language and Letters Department, 2019)
It is undeniable that humans as an active subject highly involve in colouring religion, necessarily leading to the belief in the existence of God. God is then described in accordance with certain narratives based on their knowledge and experience. Some suggest with majestic beauty through an emphasis on Jamaliyah that the narrative invites sympathy and longing for God. On the contrary, some also emphasize on Jalaliyah, so the narrative leads to fear in His punishment. This paper presents a comprehensive description of God under the literary narratives of Sufi, the practitioners of Sufism, widely known as people who emphasize on the esoteric side of religion. God, in the narrative of Sufi, is the Supreme, Most Gracious, and Loving. According to them, God manifests in various entities, so everything in the universe is 'deified'. Only the One God is worshipped while others only need to be respected. Keywords: God, literature, religion, Sufi, Sufism